Hubungan Komunikasi Interpersonal Mahasiswa dan Dosen Pembimbing dengan Motivasi Menyusun Skripsi pada Mahasiswa Komunikasi dan Penyiaran Islam - Fadhilah Nur Annisa; Santi Lisnawati; Sri Nurul Milla (IAI Nasional Laa Roiba Bogor, 2023)
Interpersonal communication is a basic activity and naturally, every human being must do this activity as a form of mutual understanding and understanding of the activities of exchanging ideas, ideas, and thoughts of two humans who carry out communication activities. In the world of education, of course, communication is the main tool in determining the success of delivering knowledge from teachers to students. As a student who is part of the world of education, the thesis is a responsibility and one of the requirements for graduation. This research was carried out to know the relationship between student interpersonal communication and thesis lecturer with the motivation to compose a thesis. The research method used is a correlational method with a quantitative approach. The population used is the 2016, 2017, and 2018, Islamic Communication and Broadcasting study program at the Faculty of Islamic Religion, Ibn Khaldun University, Bogor with a total of 59 students as respondents. Data processing using SPSS 20 with Pearson product-moment correlation analysis technique. The results obtained are significant values ​​that have been obtained on the X variable (interpersonal communication) with the Y variable (the motivation to compose the thesis) of 0.000 < 0.05. In the calculation of the value of rcount > rtable, it is obtained that 0.687 > 0.252, which can be concluded that the interpersonal communication between students and thesis lecturer with the motivation to write a thesis has a strong relationship. The interpretation that the higher the interpersonal communication relationship between students and thesis lecturer, the motivation also increases students in writing thesis. Keywords: Interpersonal Communication, Motivation, Thesis